Congenital Hyperinsulinism and Maple Syrup Urine Disease: A Challenging Combination - Azza AL Shidhani; Abdulhamid Al Hinai; Khalid Al Thihli; Hilal Al Mandhari; Saif Al Yaarubi; Irfan Ullah; Nadia Al-Hashmi; Fathiya Al Murshedi (Galenos Yayincilik, 2023)
Congenital hyperinsulinism (CHI) is the most common cause of persistent hypoglycemia in infancy. CHI is a challenging disease to diagnose and manage. Moreover, complicating the course of the disease with another metabolic disease, in this case maple syrup urine disease (MSUD), adds more challenges to the already complex management. We report a term neonate who developed symptomatic, non-ketotic hypoglycemia with a blood glucose (BG) level of 1.9 mmol/L at 21-hours of life. A critical sample at that time showed high serum insulin and C-peptide levels confirming the diagnosis of CHI. Tandem mass spectrometry done at the same time was suggestive of MSUD which was confirmed by high performance liquid chromatography. The diagnosis of both conditions was subsequently confirmed by molecular genetic testing. His hypoglycemia was managed with high glucose infusion with medical therapy for CHI and branched chain amino acids (BCAA) restricted medical formula. At the age of four months, a near-total pancreatectomy was done, due to the failure of conventional therapy. Throughout his complicated course, he required meticulous monitoring of his BG and modified plasma amino acid profile aiming to maintain the BG at ≥3.9 mmol/L and levels of the three BCAAs at the disease therapeutic targets for his age. The patient is currently 29 months old and has normal growth and development. This patient is perhaps the only known case of the co-occurrence of CHI with MSUD. Both hypoglycemia and leucine encephalopathy can result in death or permanent neurological damage. The management of CHI and MSUD in combination is very challenging.